2022
DOI: 10.13057/biodiv/d230805
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, distribution, and nest characteristics of stingless bees (Hymenoptera: Meliponini) in Baluran National Park, East Java, Indonesia

Abstract: Abstract. Rachmawati RD, Agus A, Umami N, Asgussalim, Purwanton H. 2022. Diversity, distribution, and nest characteristics of stingless bees (Hymenoptera: Meliponini) in Baluran National Park, East Java, Indonesia. Biodiversitas 23: 3890-3901. Baluran National Park is a conservation area located in Situbondo, East Java. It has become a natural habitat for many animals, including stingless bees. Stingless bees, known as klanceng in Java, are eusocial insects that produce honey and play an important role as poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…This species frequently nested in human constructs in rural and suburban areas [23], in walls, trees, and pole cavities in South Gujarat, India [24]. Accordingly, the distribution of T. laeviceps in Baluran National Park, East Java, Indonesia, revealed that the bees were distributed in all sampling sites with different habitat types: teak forest and secondary forest, savanna, mangrove habitat, and rural area [25].…”
Section: Discussionmentioning
confidence: 99%
“…This species frequently nested in human constructs in rural and suburban areas [23], in walls, trees, and pole cavities in South Gujarat, India [24]. Accordingly, the distribution of T. laeviceps in Baluran National Park, East Java, Indonesia, revealed that the bees were distributed in all sampling sites with different habitat types: teak forest and secondary forest, savanna, mangrove habitat, and rural area [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thummajitsakul et al (2013) mempublikasikan hasil urutan beberapa gen mikokondria pada jenis Tetragonula pagdeni, termasuk di dalamnya gen ATPase, COI, COII, COIII, Cytb, dan 16S rRNA. Penelitian keanekaragaman lebah tanpa sengat dengan menggunakan gen 16S rRNA juga telah dilaksanakan di Indonesia, yaitu pada Taman Nasional Halimun Salak, Jawa Barat (Pratama et al, 2023), Taman Nasional Baluran, Jawa Timur (Rachmawati et al, 2022), Kabupaten Ciamis, Jawa Barat (Purwanto dan Trianto, 2021), Yogyakarta (Trianto dan Purwanto, 2020a), dan Kota Sawahlunto, Sumatera Barat (Herwina et al, 2022).…”
Section: Amplifikasi Dnaunclassified
“…PCR profiles for A. mellifera 16SrRNA are as follows: predenaturation at 95°C for 2 min, 35 cycles (denaturation at 95°C for 30 s, annealing at 52°C for 30 s, extension at 72°C for 30 s), final extension at 72°C for 5 min and final hold at 4°C (Thummajitsakul et al 2013; Nuraini and Purwanto 2021;Rachmawati et al 2022). PCR conditions for N. apis and N. ceranae 16S rRNA are as follows: predenaturation at 94°C for 5 min, 35 cycles (denaturation at 94°C for 30 s, annealing at 58°C (N. ceranae) or 66°C (N. apis) for 30 s, extension at 72°C for 1 min), and final extension at 72°C for 10 min (Ansari et al 2017;Salkova et al 2018).…”
Section: Acknowledgementsmentioning
confidence: 99%